A Comparative Biochemical Study of Proteins Profile in Iraqi Children and Adolescent with ?-Thalassemia - M. Malik, Ali; M. Malik, Emad; MJ Al-Shammaa, Nawal; M. Al-Rubaei, Zeinab (Iraqi Journal of Pharmaceutical Sciences, 2017)
The aim of the present research is to study different protein fractions in sera of children and adolescent with β –thalassemia major and minor and to compare the results with that of healthy control.One hundred fifty children and adolescents were enrolled in this study,including 50 patients with β- thalassemia major , 50 patients with β- thalassemia minor as pathological control group and another apparently 50 healthy individuals as a control group. The age of all studied groups ranged from (4-18)years.Total protein, albumin and immunoglobulins were estimated in sera of all subjects. A Significant decrease was found in the total protein and albumin levels in sera of both major and minor thalassemic patients compared to normal groups. A Significant increase in immunoglobulin levels (IgG, IgM and IgA) was found in the sera of major and minor β-thalassemia patients compared to control.Different protein parts in sera of all subjects were detected using cellulose acetate electrophoresis.The results revealed significant reduction in β- globulin fractions in β- thalassemia major patients compared to the normal and pathological control groups. Significant elevations in γ- globulins fractions were observed in both major β- thalassemia and minor β- thalassemia as compared to normal control group. As a Conclusion the alteration in some protein parts occurred which is more obvious in major thalassemia patients compared to the normal and pathological control groups. Key words: Protein Parts , Elecrtrophoresis , β-Thalassemia